ANALISIS DE VIABILIDAD ECONÓMICA Y OPERATIVA DE LA IMPLEMENTACION DE LA CAFETERIA DELIFITNESS EN SANTA MARTA PARA EL AÑO 2024 - Altamar Figueroa, Yuli Marcela; Lopez Tarazona, Leonor de los Milagros (Universidad Antonio Nariño, 2023)
Delifitness will be a great company dedicated to the satisfaction of our clients in their healthy life, we are not only talking about people dedicated to the gym, but also people with health problems and who must eat a balanced diet for their well-being, basically we will be aimed at all kinds of customers who want to have a healthy life in general. It is a cafetería with different and special characteristics to satisfy the needs of our users and take care of their health. A place where you can eat healthy will always allow you to obtain benefits such as: Stay strong. Protects the immune system. Maintain healthy skin. Prevents osteoporosis. Importantly protects the heart. Helps to test eye problems. Maintains good physical condition Among many other benefits.We will have strategic points and locations that just by stepping on them you will feel calm, you will be able to enjoy quality time next to family or friends, where we will have the pleasure of serving you with our collaborators with excellent human quality and attention to the public. Thinking big will make giant things happen.